Law and Society Approach on Legal Protection for Victims of Domestic Violence (Universitas Negeri Semarang, 2022)
Violence in society is actually not a new thing. Violence is often carried out in conjunction with one form of criminal act, as regulated in the Criminal Code (KUHP) for example theft with violence (Article 365 of the Criminal Code), rape (Article 285 of the Criminal Code), Persecution (Article 351 of the Criminal Code). However, at this time there is a lot of domestic violence in the form of violence against wives or women. Often this act of violence is called a hidden crime. It is called so, because both the perpetrator and the victim try to keep the act a secret from public view. Sometimes it is also called domestic violence, because violence occurs in the domestic sphere. Criminal acts of domestic violence can cause victims both due to physical, psychological, sexual and neglect, so that efforts to protect victims are needed, including physical and psychological health recovery. For perpetrators of domestic violence, law enforcement efforts are needed to resolve cases of violence through the judicial process. Constraints in resolving domestic violence cases need to be overcome through the role of the government and local governments in collaboration with the community so that the implementation of the elimination of domestic violence can be realized. This study is intended to describe and analyze the legal protection for the victims of domestic violence in Indonesia by comparing some related laws and regulations such as Anti-Domestic Violence Act, Child Protection Act, Human Rights Law, and Indonesian Criminal Code.